Gas turbine combustion characteristics of H2/CO synthetic gas for coal integrated gasification combined cycle applications. (14th September 2015) - Lee, Min Chul; Yoon, Jisu; Joo, Seongpil; Yoon, Youngbin
Abstract: This paper describes the gas turbine combustion characteristics of coal-derived synthetic gas (syngas), particularly for the syngases at the Taean IGCC plant in Korea and the Buggenum IGCC plant in the Netherlands. To evaluate the combustion performance of these syngases, we conducted combustion tests with elevated temperature and ambient pressure in a GE7EA model combustor. We observed flame stability, dynamic pressure characteristics, NOx and CO emissions, temperature in the combustion chamber, and flame structures while varying the heat input and diluent integration ratio. Without dilution, Buggenum's stable regime is larger than that of Taean, since a higher hydrogen content causes sustained flames, even at a very high flame stretch rate. However, when considering nitrogen dilution, Taean's syngas has a more stable burn than that of Buggenum, since an increase in nitrogen at Buggenum has negatively affected flame stability. From the results of NOx /CO emissions and combustion efficiency, we report that both syngases are sufficient to control NOx emissions at under 5 ppm with almost complete and stable combustion; however, quantitatively, the effect of nitrogen dilution is slightly different at Taean and Buggenum due to slight differences in the H2 /CO ratio and diluent heat capacity. All the tested results and conclusions drawn are considered for optimal operation and trouble shooting at the Taean IGCC plant, which is scheduled to be complete toward the end of 2016. Highlights: Taean syngas burns more stably than Buggenum syngas due to lower N2 composition. Syngas flame exists under 82 mol% N2, the lower flammable limit by Chatelier rule. Optimal operating condition for low NOx /CO emission is 1230 °C < T ad < 1500 °C. NOx is reduced to <3 ppm when IRN2 >50%, but excessive IRN2 causes flame unstable. Syngas flame attachment/detachment is the key mechanism of combustion instability.